Polyimides (IntechOpen, 2022)
Polyimides are a new generation of polymers that exhibit excellent mechanical, thermal, chemical, and electrical properties. Hence, they are highly reliable with little change in physical properties over a long time. They are currently used for practical applications in aerospace, energy, automotive, and electronics industries. This book presents a comprehensive overview of polyimides, including their properties, synthesis, and applications, as well as future research directions and challenges.